Public Views of Dairy Calf Welfare and Dairy Consumption Habits of American Youth and Adults - Perttu, Rielle K.; Ventura, Beth A.; Rendahl, Aaron K.; Endres, Marcia I. (Frontiers in Veterinary Science, 2021)
The primary objective of this study was to explore views of dairy calf welfare and dairy product consumption habits among youth and adults. The secondary objective was to explore these constructs among a subset of parent-child pairs. Participants 5 to 17 years of age (n = 463) and 18 years old or greater (n = 1,310) completed an in-person survey at the Minnesota State Fair (St. Paul, MN, USA). A subset of these data was comprised of parent-child pairs (n = 188). The survey included questions about demographics and calf welfare, an open-ended question on ‘what dairy calves need to have a good life’, and questions about participants’ consumption of dairy products and nondairy alternative products. Content analysis was used for responses to the open-ended question. Fisher's exact test and Cohen's Kappa were used to investigate the relationships between parent-child pair responses about dairy calf welfare and consumption habits. The median age of all youth participants was 11 years, 61% were female, and 82% were urban residents. Most youth participants (94.4%) indicated that they consumed dairy products, while 47.1% consumed nondairy alternative products. Median age range of all adult participants was 45 – 54 years, 65% were female, and 82% urban residents. Most adult participants (93.7%) indicated that they consumed dairy products and 47.1% indicated that they consumed nondairy alternative products. In response to ‘what dairy calves need to have a good life,’ youth and adults most commonly focused on issues related to biological functioning (82 and 70% of youth and adults, respectively), followed by natural living (44 and 50%, respectively), humane care (30 and 20%, respectively), and affective states (5% of both youth and adults). The parent-child relationship was associated with natural living (Kappa = 0.193; P = 0.007; overall agreement = 60.6%). In addition, the parent-child relationship was associated with consumption of dairy products (P = 0.032; overall agreement = 90.4%). The results suggest that biological functioning is highly valued by the public and views of parents and their children related to natural living in dairy calves are associated.